(untitled) (Philology, 2026)
The article analyzes two Portuguese fictional texts, in which an analogy to the topic of the posthumous heroine, treated by E.A. Poe, could be traced: a short-story “Vera e o Acidente” (As Quatro Estações, 1980) by David Mourão-Ferreira and a novel Tão Longo Amor, Tão Curta a Vida (2013) by Hélder Macedo. In addition to the principal topic of the return of a lost/dead woman, both narratives are concerned with the mythic legacy (especially with the myth of Persefone).